2014
DOI: 10.1186/1756-0500-7-801
|View full text |Cite
|
Sign up to set email alerts
|

Sugar metabolism, chip color, invertase activity, and gene expression during long-term cold storage of potato (Solanum tuberosum) tubers from wild-type and vacuolar invertase silencing lines of Katahdin

Abstract: BackgroundStoring potato tubers at low temperatures minimizes sprouting and disease but can cause an accumulation of reducing sugars in a process called cold-induced sweetening. Tubers with increased amounts of reducing sugars produce dark-colored, bitter-tasting fried products with elevated amounts of acrylamide, a possible carcinogen. Vacuolar invertase (VInv), which converts sucrose produced by starch breakdown to glucose and fructose, is the key determinant of reducing sugar accumulation during cold-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Thus, an acrylamide mitigation strategy focused on developing potato cultivars with low reducing sugars will likely be the most effective approach for minimizing the acrylamide-forming potential of French fry processing potatoes. However, it is less clear whether this variety development strategy also applies to chipping potatoes as these already have very low tuber reducing sugar contents, and VInv expression during postharvest storage may differ substantially from that in Russet Burbank (Wiberley-Bradford et al, 2014). Wild potato germplasm with extremely high level of CIS resistance is available (Hamernik et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an acrylamide mitigation strategy focused on developing potato cultivars with low reducing sugars will likely be the most effective approach for minimizing the acrylamide-forming potential of French fry processing potatoes. However, it is less clear whether this variety development strategy also applies to chipping potatoes as these already have very low tuber reducing sugar contents, and VInv expression during postharvest storage may differ substantially from that in Russet Burbank (Wiberley-Bradford et al, 2014). Wild potato germplasm with extremely high level of CIS resistance is available (Hamernik et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…CIS has been widely studied in potato tubers (Foukaraki et al 2016;Mehdi et al 2013;Wiberley-Bradford et al 2016), and it has been reported that CIS occurs due to an imbalance between the metabolism of starch and sugar (Ezekiel et al 2010). The degradation pathway from starch to hexoses is complex, and several enzymes are involved in this progress, including sucrose synthase (SuSy), sucrose phosphate synthase (SPS), ADP-glucose pyrophosphorylase small subunit (AGPase), granulebound starch synthase (GBSS) (Wiberley-Bradford et al 2014). Researchers proposed that the sucrose enters into the vacuole, where it can be cleaved to glucose and fructose, which was catalyzed by acid invertase (INV) (Sowokinos 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, during cold induced storage, sucrose is converted to glucose and fructose by the vacuolar enzyme acid invertase (VInv) [31]. Therefore, harvesting time and storage condition greatly influence the levels of these reducing sugars.…”
Section: Acrylamide Formation In the Potato Model Systemmentioning
confidence: 99%